Educate, not kill: treating cancer without triggering its defenses - Škarková, Aneta; Bizzarri, Mariano; Janoštiak, Radoslav; Mašek, Jan; Rosel, Daniel; Brábek, Jan (Trends in molecular medicine, 2024)
Traditionally, anticancer therapies focus on restraining uncontrolled proliferation. However, these cytotoxic therapies expose cancer cells to direct killing, instigating the process of natural selection favoring survival of resistant cells that become the foundation for tumor progression and therapy failure. Recognizing this phenomenon has prompted the development of alternative therapeutic strategies. Here we propose strategies targeting cancer hallmarks beyond proliferation, aiming at re-educating cancer cells towards a less malignant phenotype. These strategies include controlling cell dormancy, transdifferentiation therapy, normalizing the cancer microenvironment, and using migrastatic therapy. Adaptive resistance to these educative strategies does not confer a direct proliferative advantage to resistant cells, as non-resistant cells are not subject to eradication, thereby delaying or preventing the development of therapy-resistant tumors.
Keywords: Animals; Drug Resistance, Neoplasm; migrastatics; resistance; proliferace buněk; Neoplasms; nádory; nádorové mikroprostředí; lidé; Antineoplastic Agents; dormancy; protinádorové látky; chemorezistence; transdifferentiation; metastasis; Cell Proliferation; Tumor Microenvironment; tumor reversion; zvířata; Humans